GAMBARAN JUMLAH TROMBOSIT PADA DIABETES MELITUS TIPE 2 - Alfi Budiman; Aisyara Yuliandari, Rosanna Selvia Sembiring (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2024)
Insulin resistance and hyperglycemia in type-2 diabetes mellitus result in endothelial injury. This injury causes the platelet hyperaggregation which eventually lead to platelet dyfunction. The purpose of this study was to obtain an overview of platelet count in patients with type-2 diabetes mellitus at X hospital in Pekanbaru. This was a descriptive study with retrospective design, namely taking samples from medical records. There were 58 medical data that met the inclusion and exclusion criteria consisting of 33 female patients and 25 male patients. The results of the study were the majority of patients aged > 40 years, 15 patients had thrombocytopenia and 25 patients with normal platelets had diabetes with extended period of 5–10 years, while 17 patients had thrombocytosis and 1 patient had normal platelet count with extended period of diabetes > 10 years.